2005
DOI: 10.1177/0163278705281079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Care Coordination/Home-Telehealth Program for Veterans with Diabetes

Abstract: We evaluated a Veterans Health Administration (VHA) care coordination/ home-telehealth (CC/HT) program on the utilization of health care services and health-related quality of life (HRQL) in veterans with diabetes. Administrative records of 445 veterans with diabetes were reviewed to compare health care service utilization in the 1-year period before and 1-year period post-enrollment and also examined self-reported HRQL at enrollment and 1 year later. Multivariate analyses indicated a statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 15 publications
2
93
0
Order By: Relevance
“…Previous studies of veterans with chronic conditions who used CCHT have shown lower mortality 24 and healthcare utilization [25][26][27] , as well as improved quality of life 26 and more timely receipt of care 28 . Other work has found increased time to readmission among veterans with heart failure 29 , including a dose-response relationship 30,31 .…”
Section: Va's Care Coordination Home Telehealth (Ccht) Programmentioning
confidence: 98%
“…Previous studies of veterans with chronic conditions who used CCHT have shown lower mortality 24 and healthcare utilization [25][26][27] , as well as improved quality of life 26 and more timely receipt of care 28 . Other work has found increased time to readmission among veterans with heart failure 29 , including a dose-response relationship 30,31 .…”
Section: Va's Care Coordination Home Telehealth (Ccht) Programmentioning
confidence: 98%
“…[56][57][58][59][60][61][62][63][64][65] Of these, five were reported by the same senior author with different coauthors. These VHA studies are presented here in historical order as a set, shown in Table 3.…”
Section: Vha Studiesmentioning
confidence: 99%
“…An observational study (n = 445) of the effects of the Care Coordination Home Telehealth program on use of service and quality of life was conducted among patients in the South Florida-Puerto Rico and Georgia VHA region (published in 2005). 56 The authors pointed out that diabetes was the second most prevalent condition among veterans in this region and that ''4% of the population (more than 1 million veterans, nationwide) were consuming 40% of the healthcare resources.'' 56 The analysis of utilization data was based on administrative records, starting at baseline and after 12 months of participation in the program.…”
Section: Vha Studiesmentioning
confidence: 99%
“…Outcomes analyses of CCHT in VHA have shown reduced hospitalizations, 30 percent fewer emergency room visits, a 30 percent reduction in the average number of bed days of care, improved health-related quality of life [22], and benefits in terms of satisfaction [23], use clinical outcomes [24][25], and cost. CCHT supports rehabilitation in the home and improved instrumental activities of daily living and cognitive function [25].…”
Section: Darkins Guest Editorial IXmentioning
confidence: 99%